Saline and osmotic stress differentially affects apoplastic and intracellular reactive oxygen species production, curling and death of root hair during Glycine max L.–Bradyrhizobium japonicum interaction - Muñoz, Nacira Belen; Robert, German; Melchiorre, Mariana; Racca, Roberto Walter; Lascano, Hernan Ramiro (Elsevier, 2021)
In the present study, the production of apoplastic and intracellular reactive oxygen species (ROS) and deformations of young soybean root hairs inoculated with Bradyrhizobium japonicum strain USDA138 were analyzed under saline and osmotic stress. Sustained and transient increase of apoplastic and intracellular ROS production, respectively, were observed in inoculated root hairs. The apical production of apoplastic superoxide in growing root hairs colocalized with flavonoid autofluorescence and both were relocated to the zone of maximum curvature in curled root hairs. Saline and osmotic stress had differential effects on both the production of apoplastic ROS and curling: only saline stress inhibited both processes in a dose-dependent manner. Intracellular ROS production was not altered by osmotic stress but was inhibited completely by 150 mM NaCl. In inoculated root hairs under 50 mM NaCl, the intracellular ROS levels were initially increased, but not decreased at later stages, as occurred in control conditions. Root hair death was induced by 150 mM NaCl in both inoculated and noninoculated roots and by 50 mM NaCl only in inoculated roots. Saline, but not osmotic stress, marked affects both apoplastic and intracellular ROS production, inhibiting root hair curling and inducing root hair death.